2017
DOI: 10.1126/scitranslmed.aam5441
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory monocytes expressing tissue factor drive SIV and HIV coagulopathy

Abstract: In human immunodeficiency virus (HIV) infection, persistent inflammation despite effective antiretroviral therapy (ART) is linked to increased risk of non-infectious chronic complications such as cardiovascular and thromboembolic disease. A better understanding of inflammatory and coagulation pathways in HIV infection is needed to optimize clinical care. Markers of monocyte activation and coagulation independently predict morbidity and mortality associated with non-AIDS events. In this study, we identified a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 64 publications
(86 reference statements)
3
105
0
Order By: Relevance
“…HIV-1-infected patients have elevated circulating levels of LPS, which can serve to increase transcriptional activation of proinflammatory cytokines (11,50). Elevated levels of IL-1␤ are associated with many of the AANCCs seen in HIV-1-infected patients (91)(92)(93)(94). Currently, there are multiple clinical trials assessing the safety and efficacy of anti-IL-1␤ antibodies in cardiovascular disease (95,96).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1-infected patients have elevated circulating levels of LPS, which can serve to increase transcriptional activation of proinflammatory cytokines (11,50). Elevated levels of IL-1␤ are associated with many of the AANCCs seen in HIV-1-infected patients (91)(92)(93)(94). Currently, there are multiple clinical trials assessing the safety and efficacy of anti-IL-1␤ antibodies in cardiovascular disease (95,96).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to acting as mechanical barriers leading to plate let aggregation, NETs may impact coagulation through other pathways. Both neutrophils and NETs can express TF (17,18), an essential activator of coagulation (19). By culturing unstimulated and stimulated neutrophils from chronically SIVinfected PTMs, we found that those generating NETs preferentially express high levels of TF ( Figure 2J).…”
Section: Neutrophil Extracellular Trap Production Contributes To Pathmentioning
confidence: 94%
“…Further, the coagulation activation marker correlated with virus load and monocyte TF expression in HIV‐infected patients . Interestingly, TF expression seems to be restricted to CD14 + CD16 − CCR2 + monocytes . Thrombin mediates the crosstalk between the coagulation system and the adaptive immune system at sites of vascular injury via PAR1 increasing T cell motility and proinflammatory cytokine production .…”
Section: Introductionmentioning
confidence: 96%